Conducting Polymers Functionalized with Phthalocyanine as Nitrogen Dioxide Sensors - S. D. Deshpande; S. Radhakrishnan (Sensors, 2002)
The conducting polymers such as polyaniline, polypyrrole and polythiophene were functionalized with copper phthalocyanine using chemical oxidation method. The obtained polymers viz. PANI-CuPc, PPy-CuPc and PT-CuPc were studied as chemical sensors by their response characteristics after exposure to various chemical vapors such as methanol, ammonia and nitrogen dioxide. The results obtained showed that these polymers have moderate sensitivity towards the methanol as well as ammonia vapors whereas they show tremendous sensitivity towards nitrogen dioxide vapors. The sensitivity factor of as high as 50,000 was obtained for PT-CuPc polymers in nitrogen dioxide. In comparison to this, the sensitivity factors of about 100 and 40 were obtained, when these polymers were exposed to ammonia and methanol vapors. The very high selectivity towards the nitrogen dioxide was explained on the basis of charge transfer complex formed between, the phthalocyanine donor and nitrogen dioxide acceptor molecules. On the other hand, ammonia becomes a competing electron donor in CuPc containing conducting polymers. The very low response towards the methanol may be explained on the basis very little charge transfer / interaction between CuPc containing polymers and methanol. Thus, CuPc incorporated conducting polymers have much higher selectivity than their original homopolymer.